Kosztorys audycji telewizyjnej a organizacja produkcji - Kotapski, Roman (Estimate of Television Programme Versus Production Organization, 2006)
The broadcast's budget depends on its organization production and it must include a production process. A broadcast's outline and a plan of production are important documents to prepare a budget. This article presents a budget of broadcast.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 129-141